SOCIAL WORK ETHICS ACROSS CULTURES: NAVIGATING THE TENSION BETWEEN UNIVERSALISM AND CONTEXTUALISM - Saaida, Mohammed; Olorede, Abdulgafar Abidemi; Omolade, Mathew Koledola (African Journal of Social and Behavioural Sciences, 2026)
The study is an investigation of the continuing ethical tension between the Westerncentric professional social work codes and cultural value systems that are often experienced within the globalized practice. While international standards promote universal human rights, their operationalization often reflects a Western bias toward individualism and secularism. The paper has criticized the uniform ethical approach to making ethical decisions through an examination of the "Universalism-Relativism" continuum and the display of three different case studies. The qualitative case study proposes a paradigm shift from traditional cultural competence toward ethical pluralism. Research indicates that a reflexive model of professional integrity is most effectively upheld through the prism of Cultural Humility that enables, without undermining, fundamental human rights. Findings also highlight the importance of equity-based ethics and the Triangulated Ethical Model in culturally complex contexts. The paper concludes with policy suggestions for social work boards to incorporate contextual ethical clauses into the national standards.